Research on flexible display at Ulsan National Institute of Science and Technology. (December 2017) - Park, Jihun; Heo, Sanghyun; Park, Kibog; Song, Myoung; Kim, Ju-Young; Kyung, Gyouhyung; Ruoff, Rodney; Park, Jang-Ung; Bien, Franklin
Abstract Displays represent information visually, so they have become the fundamental building block to visualize the data of current electronics including smartphones. Recently, electronics have been advanced toward flexible and wearable electronics that can be bent, folded, or stretched while maintaining their performance under various deformations. Here, recent advances in research to demonstrate flexible and wearable displays are reviewed. We introduce these results by dividing them into several categories according to the components of the display: active-matrix backplane, touch screen panel, light sources, integrated circuit for fingerprint touch screen panel, and characterization tests; and we also present mechanical tests in nano-meter scale and visual ergonomics research.